Effects of plant growth regulators and potassium on growth and yield of finger millet - Sivakumar, R; Surendar, K Krishna (Bangladesh Journal of Botany, 2020)
Impact of plant growth regulators viz., benzyl amino purine (BAP - 50 ppm), brassinolide (BL - 0.5 ppm), and nutrient like KCl (1%) alone and with combination on growth and growth analytical parameters, and yield of finger millet by foliar spray at panicle initiation stage under rainfed condition was studied in field experiment. The treatments including control, KCl, BAP, BL, KCl + BAP, KCl + BL, BAP + BL and KCl + BAP + BL and different growth and growth analytical parameters were estimated. Combination of KCl, BAP and BL registered highest root length (17.2 cm), leaf area (425.3 cm2), leaf area index (1.82) and leaf area duration (55.7 days) compared to other treatments. Higher specific leaf weight and crop growth rate were recorded by KCl + BAP, and BAP + BL, respectively. The highest grain yield of 22.5 Q/ha was recorded by KCl + BAP + BL.